Design of Horizontal Type Mangosteen Peel Flour Machine for Mangosteen Peel Processing - Rosyid Ridho (Publikasi Indonesia, 2024)
The Mangosteen fruit (garcinia mangostana L.) nicknamed the queen of fruit is one of Indonesia's superior fruits. Mangosteen fruit consists of components in the form of seeds, fruit, pulp, and fruit skin. This research aims to design a horizontal-type mangosteen peel-blowing machine. This mangosteen rind flouring machine is designed in a horizontal shape which aims to flour the dried mangosteen rind. The design process uses the Solid Work application and then the manufacturing process. Machines that have been manufactured are subjected to testing. The flouring process uses a separating cylinder and a crushing knife. Dried mangosteen skin that is put into the hopper will enter the cylinder and be crushed by a rotating blade and produce flour. The flour will come out through the output door. This machine floured the skin of the mangosteen fruit according to the initial design objectives. This research succeeded in removing the dried mangosteen peel.